1988
DOI: 10.1002/chin.198808282
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reduction of N‐Sulfonyltellurium Imines by Diphenyl Ditelluride.

Abstract: A 3:1 molar mixture of the tellurium imines (I) and diphenyl ditelluride (II) reacts to give a separable mixture of the diaryl tellurides (III), the sulfonamides (IV) and the N,N‐bis(phenyltellurenyl)sulfonamides (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…N-p-Tosyldiaryltellurimides and diaryl telluroxides possess very similar chemical properties. This is particularly true for the reactions proceeding via semipolar bond Te-N and Te-0 cleavage, i.e., for phosphines [11,12], thiols [4,12], thioamides [4,12], and hydroquinone and its derivatives [6,12]. Therefore, it is conceivable that Reaction 1 may develop by a mechanism like the one for Reaction 2 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…N-p-Tosyldiaryltellurimides and diaryl telluroxides possess very similar chemical properties. This is particularly true for the reactions proceeding via semipolar bond Te-N and Te-0 cleavage, i.e., for phosphines [11,12], thiols [4,12], thioamides [4,12], and hydroquinone and its derivatives [6,12]. Therefore, it is conceivable that Reaction 1 may develop by a mechanism like the one for Reaction 2 .…”
Section: Resultsmentioning
confidence: 97%
“…This gives rise to arenetellurinic anhydrides 5 [lo], it might be suggested that the formation of' 8 includes a homolytic cleavage of the Te-0 bond, leading to the formation of radicals. However, when the reaction was conducted in an ESR spectrometer cell, no ESR signals were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation